Who is driving land consumption? A comparison of plans and their impact on land use - Meinel, Gotthard; Henger, Ralph; Krüger, Tobias; Schmidt, Tom; Schorcht, Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Controlling settlement development, which is committed to the land-saving objective, requires precise monitoring of settlement development. This paper describes how the use of new land is related to various planning procedures in Germany. The extent to which the Federal Government, the Federal States and the municipalities contribute to land use was empirically determined on the basis of 30 representatively selected municipalities. The results of these studies show that around two thirds of Germany-wide land use is caused by municipalities within the framework of their municipal planning. Other developments resulting from planning approval procedures, for example, are driven by the Federal Government and the Federal States and contribute to one third of land use. The relatively high proportion of non-municipally induced new land use was not expected tobe as high. The result shows that efforts to save land at all spatial and planning levels are necessary in order to achieve the sustainability goals. Such investigations require comprehensive and continuously updated geometric bases for actual land use. This is the only way to measure changes in land use realistically and promptly and to verify the effects of land management. However, the ongoing methodological changes in land-use recording (geodata modelling, land-use nomenclature) and their time-delayed and different implementation in the Federal States have a negative impact on land-use monitoring.
Keywords: Land consumption; Settlement area; Area statistics; Monitoring; Planning procedures